Effect of plant protein mixtures on the microstructure and rheological properties of myofibrillar protein gel derived from red sea bream (Pagrosomus major). (November 2019) - Lin, Duanquan; Zhang, Longtao; Li, Runjing; Zheng, Baodong; Rea, Mary C.; Miao, Song
Abstract: In this study, the influence of plant protein mixtures (soy protein isolate (SPI) + peanut protein isolate (PPI), SPI + rice protein isolate (RPI), and PPI + RPI) on the microstructure, rheological properties and molecular driving forces of myofibrillar protein (MP) gels was studied. SPI could form a gel with smoother and denser network, while the structures of PPI and RPI gels were rougher, which led to the network structures of SPI + PPI and SPI + RPI gels but the disrupted structure of PPI + RPI gel. However, the SPI + RPI and PPI + RPI gels with different microstructures exhibited larger gel strength compared to the RPI gel. After mixing MP with the mixture of SPI + PPI and SPI + RPI, the mixed gels became more compact, evener and smoother, while the mixture of PPI + RPI induced more pores to the MP gel. However, G′ values of these three kinds of mixed gels were similar and much larger than that of MP gel. In addition, the molecular driving forces involved in the mixed plant protein gels and mixed MP-plant protein gels were mainly hydrophobic interactions and disulfide bonds. Graphical abstract: Image 1 Highlights: Mixing SPI with PPI or RPI formed gel network while the PPI + RPI gel was disrupted. The mixture of SPI + PPI and SPI + RPI made the MP gel more compact and smoother. The mixture of PPI + RPI induced more pores to the MP gel. Hydrophobic interactions and disulfide bonds were main molecular driving forces in mixed gels.